EFEKTIVITAS PENGGUNAAN BAHAN AJAR FLIPBOOK DALAM PEMBELAJARAN JARAK JAUH TERHADAP PARTISIPASI BELAJAR IPA DI SMP - Gafelina, Gafelina; Sari, Rika Widia; Saputra , Sadi; Wicaksono , Dirgantara (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The Covid-19 pandemic, which lasted for more than a year, had a tremendous impact on the learning process, requiring the implementation of distance learning. Various problems that emerged during the implementation of distance learning (PJJ) demanded efforts to overcome them. This study aims to determine the effectiveness of using Flipbook teaching materials integrated with the Google Classroom platform in distance learning, as well as to provide an overview of students’ responses to the effectiveness of online learning in relation to their learning interest. The research method used was a descriptive method, which describes the implementation of distance learning using Flipbook teaching materials. The Flipbook teaching materials embedded in the Google Classroom platform as a Learning Management System (LMS) feature an attractive layout, are easy to use, allow students to understand the learning material more easily, and contain clear text and supportive images that enhance comprehension. The selection of appropriate media and the students’ motivation to obtain good grades and knowledge served as supporting factors that contributed to positive student responses. Additionally, the level of student activeness and engagement during the online learning process became an indicator that influenced their learning interest, particularly in science subjects. Based on the collected data, students gave a very positive response regarding the effectiveness of online learning toward their learning interest. The advantages of using Flipbook teaching materials, as shown by questionnaire results, received a “good” rating, and students’ level of understanding of the learning material achieved an average score above the minimum competency criteria (KKM). ABSTRAKTerjadinya masa pandemi Covid-19 yang berlangsung lebih dari setahun menimbulkan pengaruh yang luar biasa dalam proses pembelajaran, sehingga harus dilakukan pembelajaran jarak jauh. Berbagai permasalahan yang muncul dalam pelaksanaan PJJ, diperlukan upaya untuk mengatasinya. Tujuan penelitian ini untuk mengetahui efektivitas penggunaan bahan ajar Flipbook dengan platform Google Classroom dalam pembelajaran jarak jauh untuk memberikan gambaran tentang respon siswa terhadap efektivitas pembelajaran daring pada minat belajar siswa. Metode penelitian yang digunakan adalah metode deskriptif, yang mendeskripsikan pelaksanaan pembelajaran jarak jauh dengan penggunaan bahan ajar Flipbook. Bahan ajar Flipbook yang disematkan dalam platform Google Classroom sebagai LMS (Learning Management System) memiliki tampilan yang menarik, mudah digunakan, materi pelajaran mudah dipahami, mengandung teks yang jelas serta gambar yang ditampilkan mendukung pemahaman materi pelajaran. Pemilihan media yang tepat dan keinginan untuk mendapatkan nilai dan pengetahuan menjadi fakor penunjang siswa memberikan respon yang baik. Serta tingkat keaktifan dan keterlibatan siswa selama proses pembelajaran daring berlangsung menjadi tolak ukur yang menarik minat belajar siswa khusunya pada mata pelajaran IPA. Berdasarkan pada data yang telah dikumpulkan menunjukkan kategori respon yang sangat baik telah diberikan siswa terhadap efektivitas pembelajaran daring terhadap minat belajar siswa. Kelebihan penggunaan bahan ajar Flipbook berdasarkan hasil angket menunjukkan predikat penilaian “baik”, serta tingkat pemahaman peserta didik terhadap materi pelajaran diperoleh nilai rata-rata di atas KKM.